Aquatic macrophyte distribution in relation to water and sediment conditions in the Itaipu Reservoir, Brazil - Bini, L. M.; Thomaz, S. M.; Murphy, K. J.; Camargo, AFM (Kluwer Academic Publ, 1999)
Aquatic macrophyte community distribution along the eastern shoreline of the Itaipu Reservoir (one of the South America's largest impoundments) is described in relation to limnological and sedimentological factors. The central body of the reservoir is mesotrophic, while the arms (flooded influent river valleys) along the eastern shore may be oligo-mesotrophic to eutrophic, depending on time of year and sub-catchment characteristics. Macrophyte community composition and species cover were surveyed at 30 sites in four arms, in relation to sediment total P and organic matter; underwater light regime; and water total P and Kjeldahl N concentration, alkalinity, conductivity, depth and pH. Seventeen euhydrophyte and six emergent macrophyte species were recorded. Large stands of Egeria najas dominated the euhydrophyte vegetation, together with free-floating weed species (Pistia stratiotes Linn., Salvinia auriculata Aublet and Eichhornia crassipes (Mart.) Solms.). Canonical Correspondence Analysis of the data showed that two sets of variables were important predictors of aquatic macrophyte community structure. Floating macrophyte assemblage was closely related to concentration of nutrients in both water and sediment, while light penetration was the strongest predictor of submerged species occurrence. Although a large number of potential nuisance species were present, dense growths were restricted to shallower areas of the Itaipu Reservoir, causing localised problems. The possibility of increasing interference by these plants with fisheries, recreational use, transport and hydroelectricity generation suggests a need for continued monitoring of weed distribution and abundance, and investigation of appropriate management measures.
Keywords: freshwater macrophytes; reservoirs; South America; aquatic weeds